The Shooting Technique Uses The Inner Foot In The Game Of Football - Nur, Muhammad; Awal, Asri; Hafid, Erwan (Sains Global Institut, Indonesia, 2023)
This study aims to determine shooting techniques using the inner foot in football games. This research is quantitative research with a descriptive approach. The method in this study uses descriptive statistics with test and measurement techniques. The population in this study was all students of SMA 11 Sinjai. The sampling technique uses random sampling, so the number of samples in this study is 20 students. The test instrument used in this study is a basic football-playing skill test instrument according to Nurhasan which has been tested for validity: shooting of 0.779 and 0.868. Data analysis uses quantitative description with percentages. The overall data of this study shows that the ability to shoot using the inner foot in football games is in a good category.